Spanish validation of the pure procrastination scale: dimensional structure, internal consistency, temporal stability, gender invariance, and relationships with personality and satisfaction with life - Guilera, Georgina; López-Martínez, Maria Dolores; Barrios, Maite; Hidalgo, María Dolores; Steel, Piers; Gómez-Benito, Juana (Frontiers in Psychology, 2024)
The objective of the current study was to adapt and validate the Pure Procrastination Scale (PPS) for the Spanish adult population. Procrastination can have numerous consequences in daily life, making it essential to have reliable and valid instruments for measuring procrastination. Thus, this study was conducted to address this need. The sample consisted of 596 adults aged 18-83 years (M = 35.25, SD = 13.75). In addition to the PPS, participants completed two procrastination measures, namely the Irrational Procrastination Scale and the Decisional Procrastination Questionnaire, alongside the Big Five Inventory and the Satisfaction with Life Scale. The results of the confirmatory factor analysis revealed a three-factor structure of the PPS. The examination of the reliability of scores in terms of internal consistency and temporal stability showed satisfactory results for the PPS scores. Moreover, gender invariance was observed at the scalar level. Finally, the PPS scores correlated with other measures of procrastination, personality traits, and satisfaction with life in the expected direction and magnitude. In conclusion, the Spanish PPS offers valid and reliable scores when administered to adult population.